2021
DOI: 10.3354/esr01150
|View full text |Cite
|
Sign up to set email alerts
|

Bright spots for research and conservation of the largetooth sawfish Pristis pristis in Colombia and Panamá

Abstract: Sawfishes are considered one of the most endangered families of fishes globally. Their diadromous ecology and vulnerability to fishing nets have brought most populations to the brink of collapse. Conservation of surviving populations is hindered by limited knowledge of historic and contemporary distribution. Colombia and Panamá are 2 of 22 countries considered as high priority for the development of species-specific national legal protection of the Critically Endangered largetooth sawfish Pristis pristis. To c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Panama and Colombia have some of the highest rates of annual rainfall in the world, maintaining many river deltas and estuaries with low salinities (Fiedler & Talley, 2006; López‐Angarita, Cubillos‐M, et al., 2021), yet Central America is one of the regions where climate change models consistently predict increases in temperature and decreases in precipitation during the wet season (Ward et al., 2016). These changes will alter estuaries and lagoons, with some potentially becoming incorporated into the sea.…”
Section: Discussionmentioning
confidence: 99%
“…Panama and Colombia have some of the highest rates of annual rainfall in the world, maintaining many river deltas and estuaries with low salinities (Fiedler & Talley, 2006; López‐Angarita, Cubillos‐M, et al., 2021), yet Central America is one of the regions where climate change models consistently predict increases in temperature and decreases in precipitation during the wet season (Ward et al., 2016). These changes will alter estuaries and lagoons, with some potentially becoming incorporated into the sea.…”
Section: Discussionmentioning
confidence: 99%
“…Blanco & Niño (2022) accounted for 85 species of elasmobranchs, 36 rays, and 49 sharks in the Mexican Caribbean. However, baseline information is scant for chondrichthyans, including sawfishes, and the expansion of such data could prove a vital progression towards their conservation and future management (Koubrak, 2018; Poulakis & Grubbs, 2019; López et al, 2021; Becerril et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…They have been an important fisheries resource as well as having culinary and medicinal uses, along with use as cultural trophies and in ritual practices (Gonzalez, 2005; Bonfil et al, 2017; Bonfil et al, 2018). Historically, sawfishes were common in food webs of estuarine, lagoonal, and coastal habitats spanning tropical and subtropical latitudes across the globe (French & Naylor, 2018; López et al, 2021). Today, however, sawfishes ( Pristis spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Our results when evaluating ethnoichthyology in a broad manner indicate that most research was carried out in marine ecosystems, as reported by Ladislau et al (2021). This reflects the number of Elasmobranchs and Chimaeras species that occur in these environments, as most species are exclusively marine, although part of part of their life cycles may take place in estuarine environments (Ebert et al 2021;Gomes et al 2019), with the exception of some stingrays (Potamotrygonidae), restricted to freshwater (Lucifora et al 2022;Rosa et al 2008), Carcharhinus leucas (Heupel and Simpfendorfer 2007) and Pristis pristis (López-Angarita et al 2021;Whitty et al 2017), which can be found in estuarine and eventually freshwater environments. However, few of the articles retrieved here focused on freshwater environments.…”
Section: Geographic Distributionmentioning
confidence: 99%